2019
DOI: 10.1249/jsr.0000000000000613
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Considerations for Athletes with Physical Disabilities

Abstract: Nutrition, which is an important factor that improves physical performance, has a major place in the lives of both disabled and nondisabled athletes. The main purpose of nutritional assessment of disabled athletes is to assess the individual's consumption to determine the insufficiencies and to suggest the necessary changes to design the most appropriate nutrition plan. Nutrition strategies play a key role in confirming the performance of disabled athletes. Considering the nature of the disability and the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…During prolonged exercise, the carbohydrate oxidation in spinal cord injured individuals is higher than when compared to individuals without spinal cord injury (Jung & Yamasaki, 2009). Thus, inadequate carbohydrate intake causes adverse effects such as reduced muscle glycogen store and increased cramps and injuries, causing muscle weakness and reduced athletic performance (Islamoglu & Kenger, 2019). Thus, nutritional periodisation is the strategy that identifies the stage in training that the athlete is at, and describes the particular nutritional requirements considering the duration, intensity, and total volume of training at that stage (Ruettimann et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…During prolonged exercise, the carbohydrate oxidation in spinal cord injured individuals is higher than when compared to individuals without spinal cord injury (Jung & Yamasaki, 2009). Thus, inadequate carbohydrate intake causes adverse effects such as reduced muscle glycogen store and increased cramps and injuries, causing muscle weakness and reduced athletic performance (Islamoglu & Kenger, 2019). Thus, nutritional periodisation is the strategy that identifies the stage in training that the athlete is at, and describes the particular nutritional requirements considering the duration, intensity, and total volume of training at that stage (Ruettimann et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Able-bodied athletes are advised to limit their total fat intake to less than 30% of their total energy intake [ 12 ], and this guideline is currently being applied to para-athletes in the absence of total fat intake guidelines specific for para-athletes [ 36 ]. The high fat intake of the participants (males: 39.7 (37.4%–41.6%), females: 42.1 (39.0%–45.3%)) in the present study is similar to the reported intakes (44.05% ± 8.0%) of female amputee national-level wheelchair basketball athletes [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary proteins affect muscle protein synthesis in the recovery process, and if not met, this can result in muscle loss and negative nitrogen balance [ 21 ]. Therefore, given the lack of recommendations for athletes with disabilities, the use and need for protein after exercise are similar to those of able athletes [ 22 , 23 ]. In contrast, a previous study suggested that compared to able athletes, athletes with disabilities will have lower protein intake because their muscle activity is lower and their overall energy requirements are reduced [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, frequent deficiencies can be seen in athletes with disabilities, with up to 51% of Canadian and American athletes reporting insufficient levels of vitamin D [ 31 ]. This deficiency may also affect the performance of exercise [ 22 ], especially in athletes with spinal cord injuries, which may increase the risk of osteoporosis because of excessive bone absorption and reduced bone formation. Vitamin E is also present in the cell membrane and plays a special role in preventing skeletal muscle damage as a major antioxidant [ 32 ].…”
Section: Discussionmentioning
confidence: 99%